Divergent and reticulate evolution in closely related species of Sphagnum section Subsecunda - Shaw, A. J. (2014)
The Sphagnum subsecundum complex includes a group of closely related, morphologically intergrading species in section Subsecunda. Nucleotide sequences from six genes (four nuclear and two chloroplast) were obtained from 74 populations representing all the putative species in this complex (S. denticulatum, S. inundatum, S. lescurii, S. subsecundum) to determine if the morphologically-defined taxa represent genetically distinct units. Sampling included populations from North America, Europe, and Asia. Parsimony analyses resolved two major groups of populations, one containing only North American plants (plus one from northern Russia) and the other containing all but two of the European samples, a few from North America, and one from Japan. Two of the four morphospecies occurred in both groups. Shimodaira-Hasegawa (SH) tests indicate that monophyly of S. inundatum, S. subsecundum, and S. lescurii can be rejected, whereas monophyly of S. denticulatum cannot be rejected with our data. Intragenic recombination was detected in both groups of populations, but was substantially higher in the “American” group. Because recombination calls into question the applicability of character-based phylogenetic methods, including parsimony, molecular similarity among populations was estimated using neighbor-joining. Neighbor-joining also resolved geographically correlated groups and corroborated the conclusion that morphologically defined species do not form genetically coherent groups. Groups of populations more closely reflect geographic than morphological patterns.